THU0499 Neutrophil Extracellular Traps (NETS): A Shared Feature of Acute Microcrystalline Arthritis. (15th July 2016) - Bardelli, M.; Lorenzini, S.; Baldi, C.; Simpatico, A.; Gamberucci, A.; Berti, G.; Garcia Gonzalez, E.; Galeazzi, M.; Selvi, E.
Abstract : Background: Neutrophil extracellular traps (NETs) are web-like structures, composed of nucleic acids, histones and granular enzymes, including myeloperoxidase and elastase, that have a physiological crucial role in innate immunity response by trapping microbes. In addition, NETs have been identified as regulators of many inflammatory and autoimmune disorders, including crystal-induced arthritis.[1, 2] In particular, a key role in the pathogenesis of gout flares has been postulated for NETs. During gout attacks, NET aggregates should package MSU crystals with a concomitant degradation of proinflammatory cytokines, leading to the rapid resolution of the inflammatory phase.[3] Objectives: To evaluate NET expression in synovial fluid from acute CPPD arthritis and to compare NET release between acute MSU and CPPD arthritis. Methods: Synovial fluid was collected from patients with active gout or pseudogout attack (n=5 for each group) and immediately centrifuged (805 rad) to separate cells from supernatant. Polymorphonuclear leukocytes were counted and immediately processed for morphological evaluation under transmission electron microscopy (Zeiss EM 109; 4000x). NET expression was evaluated by fluorescence microscopy using SYTOX Green (Life Technologies) and neutrophil elastase specific antibody (ABCAM). Fluorometric quantification of NET components, DNA and neutrophil elastase, was performed in supernatant (Cary Eclipse Varian; exc/em 503/526). Results were normalized to cells/mm 3 . Peripheral blood neutrophils from healthy donors stimulated with PMA were used as positive controls whereas PMA-untreated neutrophils were used as negative ones. All the experiments were performed according with Helsinki guidelines. Results: Extracellular material morphologically compatible with NETs was observed by electron microscopy in samples from both acute MSU and CPPD arthritis. NET structures were confirmed by the presence of extracellular DNA and neutrophil elastase at immunofluorescence. Fluorometric quantification of extracellular DNA and neutrophil elastase showed an increased NET release in both gout and pseudogout samples compared with negative controls (p<0.01). No significant differences in NET release were measured between acute MSU and CPPD arthritis samples. Conclusions: Beyond confirming NETs in acute MSU arthritis, we have evidence of NET release in synovial fluid from acute CPPD arthritis. Our preliminary data suggest that the release of NETs could be a common physiophatological pathway to both crystral induced arthropaties. Disclosure of Interest: None declared